Faringoamigdalitis estreptocócica - Gutiérrez C., Daniela; León S., Karen; Bahamonde S., Héctor (Revista Hospital Clínico Universidad de Chile, 2011)
Streptococcal pharyngitis is common in children and adolescents. It is strongly suggested by the presence of fever, tonsillar exudate, tender enlarged anterior cervical lymph nodes and absence of cough (Centor criteria). Available diagnostic tests include throat culture and rapid antigen detection testing. Throat culture is considered the diagnostic standard, although the sensitivity and specificity of rapid antigen detection testing have improved significantly. The modified Centor score can be used to help physicians decide which patients need no testing, throat culture/rapid antigen detection testing, or empiric antibiotic therapy. Treatment of acute streptococcal pharyngitis is important for preventing acute rheumatic fever and suppurative complications, hastening illness resolution, and reventing transmission. Penicillin (10 days of oral therapy or one injection of intramuscular benzathine penicillin) is the treatment of choice because of cost, narrow spectrum of activity, and effectiveness. Amoxicillin is equally effective and more palatable. Erythromycin and first-generation cephalosporins are options in patients with penicillin allergy.